Orange Technology for Humanistic Innovation in Higher Education - Shesilia Wibowo; Irene Apriani Widjaya; Jihan Zanubiya; Richard Evans; Untung Rahardja (Jurnal MENTARI: Manajemen, Pendidikan dan Teknologi Informasi, 2026)
Amidst the rapid adoption of technology in education, a crucial challenge arises regarding the risk of dehumanizing learning. This study examines Orange Technology as a humanistic innovation approach that seeks to balance digital advancement with human values. Using a qualitative descriptive approach, this research analyzes literature from academic journals and technology education reports, which are then evaluated through a SWOT framework. The analysis results indicate that while Orange Technology holds significant potential to enhance students’ mental well being, digital empathy, and emotional engagement, its implementation faces significant challenges, including limited human resources and inadequate ethical regulations. Therefore, it is concluded that the success of this implementation requires a holistic strategy encompassing investment in human resource training, policy development, and interdisciplinary collaboration. This innovation model has strategic relevance to the Sustainable Development Goals (SDGs), particularly Goal 4 (Quality Education). By focusing on character development and mental well-being, this research contributes to creating an education system that is not only efficient but also inclusive, equitable, and relevant to the holistic needs of future generations.